Grain Inorganic Arsenic Content in Rice Managed Through Targeted Introgressions and Irrigation Management - Fernández-Baca, Cristina P.; McClung, Anna M.; Edwards, Jeremy D.; Codling, Eton E.; Reddy, Vangimalla R.; Barnaby, Jinyoung Y. (Frontiers in Plant Science, 2021)
Arsenic (As) accumulation in rice grain is a significant public health concern. Inorganic arsenic (iAs) is of particular concern because it has increased toxicity as compared to organic As. Irrigation management practices, such as alternate wetting and drying (AWD), as well as genotypic differences between cultivars, have been shown to influence As accumulation in rice grain. A two-year field study using a Lemont×TeQing backcross introgression line (TIL) mapping population examined the impact of genotype and AWD severity on iAs grain concentrations. The “Safe”-AWD (35 to 40% soil volumetric water content (VWC)) treatment did not reduce grain iAs levels, while the more severe AWD30 (25 to 30% VWC) consistently reduced iAs concentrations across all genotypes. The TILs displayed a range of iAs concentrations by genotype, from less than 10 to up to 46 µg kg-1 under AWD30 and from 28 to 104 µg kg-1 under Safe-AWD. TIL grain iAs concentrations for flood treatments across both years ranged from 26 to 127 µg kg-1. Additionally, seven quantitative trait loci (QTL) were identified in the mapping population associated with grain iAs. A subset of eight TILs and their parents were grown to confirm field-identified grain iAs QTL in a controlled greenhouse environment. Greenhouse results confirmed the genotypic grain iAs patterns observed in the field; however, iAs concentrations were higher under greenhouse conditions as compared to the field. In the greenhouse, the number of days under AWD was negatively correlated with grain iAs concentrations. Thus, longer drying periods to meet the same soil VWC resulted in lower grain iAs levels. Both the number and combinations of iAs-affecting QTL significantly impacted grain iAs concentrations. Therefore, identifying more grain iAs-affecting QTL could be important to inform future breeding efforts for low iAs rice varieties. Our study suggests that coupling AWD practices targeting a soil VWC of less than or equal to 30% coupled with the use of cultivars developed to possess multiple QTL that negatively regulate grain iAs concentrations, will be helpful in mitigating exposure of iAs from rice consumption.